Awareness and Acceptance of Premarital Screening Test and Genetic Counseling Program in Riyadh area, Saudi Arabia - Mohammed Zaid Aljulifi, Mona Abdullah S Almutairi, Mohammad Shakil Ahmad, Sawsan M Abdall, May Musaad M Alelaiwi, Fatimah Lailay M Almutairi, Sara Mohammad H Alkahtani, Abdulmalik B Albaker (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Saudi Arabia has a high prevalence of hereditary diseases such as thalassemia and sickle cell disease that estimated the prevalence of 1.5%-17% for each -thalassemia and SCD respectively according to the general statistics organization. For that Saudi Arabia implemented Premarital screening and genetic counseling (PMSGC) program, since 2004, which aims to limit the spread of some genetic blood diseases and infectious diseases along with reducing pressure over health institutions, avoiding the social and psychological problems for families whose children suffer and reducing the family and community’s financial burdens. Objective: The study aimed to assess the knowledge, awareness, acceptance, and attitude of the national premarital screening programs in Al-Riyadh area, Saudi Arabia. Methodology: A cross-sectional community-based study was conducted among 564 participants from the ages of 18 and over across 8 cities in the Riyadh area, Saudi Arabia from October 2019 to April 2020. Data collected by pretested preceded paper and electronic questionnaire, which consist of three main parts. The first part focused on respondents’ sociodemographic and general characteristics, the second part was concerned with knowledge and awareness while the third part explored attitude towards the national PMSGC program. Results: The overall knowledge level among the participants was 35.8% had good knowledge, 35.1% had moderate knowledge and 29.1% had poor knowledge. A significant association between the level of knowledge and both age and marital status groups was observed (p = 0.005) and (p = 0.014) respectively. The participants group with 31-40 age and the married group had the best knowledge compared to the other groups. The overall awareness level was 36.5% had good awareness, 49.8% had moderate awareness, while only 13.7% had poor awareness. A significant association between the level of awareness and level of education was observed (p = 0.041), which revealed that the level of an educated group with the best awareness level was College-educated participants. Out of 564 participants, 542 (96.10%) support and accept PMSGC in Saudi Arabia along with 92.38% of participants who had a positive attitude toward the program. Conclusion: This study highlights that knowledge of the general population in the Al Riyadh area regarding the PMSGC program was good, while they have a moderate awareness regarding the program. These results indicate that there is a need for more information and education regarding the PMSGC program.